Comparison of the efficacy and safety of first-line treatments for of advanced EGFR mutation-positive non-small-cell lung cancer in Asian populations: a systematic review and network meta-analysis - Chen, Wei; Miao, Julian; Wang, Ying; Xing, Wenzhong; Xu, Xiumei; Wu, Rui (Frontiers in Pharmacology, 2023)
Background: According to the 2023 guidelines for treating non-small-cell lung cancer (NSCLC), first-line treatment and recent agents for the treatment of epidermal growth factor (EGFR) mutation-positive locally advanced or metastatic NSCLC were hereby compared. Drugs involved in the study included tyrosine kinase inhibitors (TKIs), angiogenesis inhibitor, and chemotherapy. Considering the different efficacy and safety of drugs in various species, the optimal regimen should be necessarily determined, and the safety of first-line treatments in the Asian population should be assessed. Methods: PubMed, Embase, the Cochrane Library, Web of Science and China National Knowledge Infrastructure (CNKI) were systematically searched to get these randomized controlled trials (RCTs) research data from inception to February 01, 2023. Taking the Asian population as a study target (Asians accounted for more than 50%), network meta-analysis (NMA) and the surface under the cumulative ranking curve (SUCRA) were used for comparison and ranking, respectively. Results: A total of 19 RCTs involving 5,824 patients and 14 treatments were included. The primary outcomes of this study were PFS, and other results had OS, DCR, ORR, AE, ≥ 3AE and SAE. For PFS, all regimens containing TKIs (monotherapy/combined with other therapies) or bevacizumab plus chemotherapy (Bev plus Ch) were significantly superior to basic chemotherapy (compared with Ch, HR: 0.09-0.61, p < 0.05). Superior therapies were erlotinib plus bevacizumab (Erl plus Bev) (SUCRA 0.94) and erlotinib plus ramucirumab (Erl plus Ram) (SUCRA 0.93). Regarding OS, no significant difference was observed in first-line treatments strategies between groups. Meanwhile, there was also was no significant difference in DCR of the first-line treatment strategy between the groups. Regarding ORR, the top three treatments were Erl plus Bev (SUCRA 0.85), Erl plus Ram (SUCRA 0.76), and Gef plus Ch (SUCRA 0.74). Erlotinib (Erl) (SUCRA 0.97) ranked first in ≥ 3AE, and Osi (SUCRA 0.91) ranked first in SAE. Conclusions: Based on the analysis of survival benefits, tumor burden response, and safety, furmonertinib (Fur), Osi, and aumolertinib (Aum) may be the best regimen for Asian patients. However, Erl plus Bev and Erl plus Ram have the best survival benefit in PFS.